The prevalence of BMI status and household food insecurity among primary school children in Kuantan, Pahang - Ab Ghalib, Halimatun Saadiah; Sidek, Suriati; Mohd Abu Bakar, Wan Azdie; Yahya, Noor Atirah; Mat Ya, Roselawati; Abdul Rahman, Rozlin (2018)
In Malaysia, the prevalence of childhood obesity is increasing in trend and recently food insecurity was found to be associated with obesity. Therefore, the present study aims to determine the prevalence of household food insecurity and BMI status among primary school children in Kuantan, Pahang. A cross-sectional study was conducted from July 2017 until November 2017 in Kuantan. Twenty primary schools were selected randomly with 797 school children aged between 7 to 11 years old were recruited in this study. There are 367 boys (46.05%) and 430 (53.95%) girls included in the study. The subjects were recruited from six sub districts in Kuantan which included Kuala Kuantan (n=540), Penor (n=20), Beserah (n=49), Ulu Lepar (n=22), Sungai Karang (n=145) and Ulu Kuantan (n=21). The anthropometric data of the children were measured using Rossmax Premium Digital Weighing Scale with Body Fat Analyzer (WF260) for weight and portable height measurement SECA Stadiometer (Model 213) for height. BMI-for-age (BAZ) z-scores were obtained using AnthroPlus® software. Categories of BMI status were based on World Health Organization (WHO) Child Growth Standard. The household food insecurity was assessed using Radimer/Cornell Hunger and Food Insecurity Instrument and answered by children’s caregivers. The results show that the prevalence of normal weight, obese, overweight and thinness/wasting are 64.37% (n=513), 15.93% (n=127), 12.05% (n=96) and 7.65 % (n=61), respectively. Meanwhile, for the prevalence of food insecurity, 24.22% (n=193) were food secure and 75.78% (n=604) were food insecure. For food insecure category, 36.4% (n=289) were household food insecure, 5% (n=40) were individual food insecure and 34.5% (n=275) were in child hunger category. This study showed that there are double burden situation in which both under-nutrition and over-nutrition are coexist and there is a high prevalence of household food insecurity in Kuantan. Therefore, proper intervention should be enforced to address these concerns.